2021
DOI: 10.3390/su13126839
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ethical Marketing in Driving Consumer Brand Relationships and Brand Loyalty: A Sustainable Marketing Approach

Abstract: This research is focused on studying the impact of ethical marketing practices on value-adding product sustainability and customer brand relationship sustainability. It further investigates the consequent effects of value-adding product sustainability and customer brand relationship sustainability on brand loyalty. Data for this study were collected from a sample of 1500 customers having multiple interactions with goods and brands of retail organizations in Pakistan. We employed structural equation modeling (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 86 publications
(133 reference statements)
3
30
0
1
Order By: Relevance
“…In the general case, the value of kurtosis and skewness falling within the range of −2 to +2 indicates that data is approximately normally distributed. However, in multivariate normality, the multivariate value for kurtosis should be less than 5 to assume that data is approximately normally distributed [70]. Table 1 demonstrates the normality results, and the multivariate kurtosis is less than 5 thresholds for each of the factors.…”
Section: Assessment Of Normalitymentioning
confidence: 99%
“…In the general case, the value of kurtosis and skewness falling within the range of −2 to +2 indicates that data is approximately normally distributed. However, in multivariate normality, the multivariate value for kurtosis should be less than 5 to assume that data is approximately normally distributed [70]. Table 1 demonstrates the normality results, and the multivariate kurtosis is less than 5 thresholds for each of the factors.…”
Section: Assessment Of Normalitymentioning
confidence: 99%
“…A study on the factors that influence the purchase of mobile phones by young adults in Pakistan [69], identified that the price, attractiveness and technological innovation of the equipment are determinants in the purchase decision process. However, the authors recognize that after-sales service (warranty, technical assistance, repair, exchange) has a lesser influence on young adults.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In turn, Ref. [69] argue that ethical marketing practices of retail organizations in Pakistan, which affect the loyalty in interactions between companies and consumers, influence the value-adding product sustainability, as well customer-value brand relationship sustainability, thereby potentially achieving sustainable brand loyalty.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These findings also provide additional insight into the ethical marketing literature where the majority of studies focused on the adverse effect of firm's unethical behaviors on their financial performances and brand equity that directly impairs sustainable customer relationships [94][95][96]. Adopting an unethical manipulation of online reviews by firms or platform providers consequently leads to an adverse effect on the focal firms and platform providers by reproducing more negative reviews for potential consumers.…”
Section: Discussionmentioning
confidence: 81%